Data Hiding Using Ycbcr-DWT in Addition to Noise - S, Maheswari; Reeba Korah, Dr (International Journal of Engineering and Technology, 2018)
An ability of hiding the important informationâ€™s like image, audio, video files into the digital media is termed as steganography. Steganography helps to attain secret communication by using variety of conventional techniques like spatial domain method, spread spectrum method and so on. In various file formats, the data hiding has undergone by these techniques but the retrieval of the secret message from the cover is not efficient with these methods. The proposed approach mainly uses YCbCr color space for conversion. A color space conversion provides an efficient transmission of color information. Secondly, a frequency domain approach of Discrete Wavelet Transformation is applied after color conversion for four level of decomposition for secret data embedding. In this approach, the converted YCbCr color space image is used as a cover image which aims to segregate illumination and chrominance component of the original input color image. And in the high intensity red layer of the cover image, the secret information is embedded in this method. In addition, this methodology is used for analysing the proposed process by superimposing of noise and exclusive of different noises. In this work, the algorithm proposed is compared with existing LSB technique and provides better PSNR measure than the existing method.Â Â